PENERAPAN MEDIA PEMBELAJARAN KARTU BERGAMBAR DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI 4 TANJUNG AMAN - Prihatmojo, Agung (LPPM STKIP PGRI Bandar Lampung, 2019)
The media is a communication tool for teacher interaction with students which is a series of teaching and learning activities in schools. In the learning process the teacher has obstacles in conveying knowledge to students. The teacher needs media to be able to help attract the attention of students so that learning objectives are achieved. Picture card learning media can help teachers effectively achieve learning objectives in the teaching and learning process. This study applies a picture card learning media to students in class V SD Negeri 4 Tanjung Aman. The aim is to find out the improvement in student learning outcomes after the teacher applies the pictorial card learning media to fifth grade students of SD Negeri 4 Tanjung Aman. In this study using a design that is the Initial Test - The Final Group Single Test (The One Group Pretest - posttest). The learning outcomes in this study were obtained by the fifth grade students before and after the implementation of the pictorial card media, to find out the improvement in the learning outcomes of the fifth grade students of SD Negeri 4 Tanjung Aman. shows that the mean or posttest average is higher than the pretest. Mean posttest 62.22 and mean pretest 46.25, so there is an increase in learning outcomes after the application of the pictorial card media to fifth grade students of SD Negeri 4 Tanjung Aman.